PENGARUH EFIKASI DIRI DAN KECERDASAN TINGKAT EMOSI TERHADAP PENGAMBILAN KEPUTUSAN KARIR MAHASISWA TINGKAT AKHIR PROGRAM STUDI ADMNISTRASI UPN “VETERAN” JAWA TIMUR - Maharani Ikaningtyas (Journal Publicuho, 2022)
The current era of globalization also demands progress from all aspects that greatly support the needs of everyday life. One of them is the development of education or education related to this matter which is able to have a positive impact on students. The purpose of this study was to determine how self-efficacy and emotional intelligence affect career decision making for final year students of the UPN "Veteran" East Java administration study program. This study uses a quantitative approach. The researcher used the Linkert scale with 5 points in linear. Based on the results of research that has been carried out by researchers, there are several conclusions. The results of the study have shown that there is a positive and significant influence between the variables of self-efficacy on career decision making. There is a positive and significant influence between emotional level intelligence variables on career decision making. And there is a significant positive effect, the hypothesis testing of self-efficacy and emotional intelligence on career decision making is accepted. Thus the conclusion is that there is a significant positive effect simultaneously on self-efficacy and emotional intelligence on career decision making